Good Personality Santri sebagai Produk Internalisasi Pembelajaran KitabKifayatul Atqiya’ di Kota Santri Sedan Rembang - Ja’far Shodiq Hibatullah; Ikhda Khullatil Mardliyah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
Studying the Turath book in Islamic boarding schools is the primary source of learning. The actualization of learning the yellow book covers all aspects of life, including moral life. Studying the book Kifayatul Atqiya teaches related morality and Sufism to the current context of moral degradation. This qualitative descriptive research uses data source search techniques through events, interviews, and document studies. Using source triangulation and the Creswell model, the method uses observation and data validity. The results of the research show that the students' good personality is formed by internalizing the learning of the book Kifayatul Atqiya, namely about patience, taubah, qana'ah, zuhud, tawakal, sincerity, keeping time, guarding your tongue, hard work and honesty. Then, the learning is contextualized with students in Santri Sedan Rembang and character through the Good Personality theory, namely affection, attachment, quality relationships, and achievement.